Design of a straw picking and cutting device - Xu, Kai; Ge, Yanyan; Xiao, Maohua; Kang, Min; Ni, Jie; Wang, Jinwu (International Journal of Agricultural and Biological Engineering, 2021)
In order to improve the effective recovery of straw, a new type of straw picking and cutting device was designed. A new type of roller moving knife mechanism was used which can realize simultaneous picking and cutting. A hammer claw was used to pick up and cut straw for the first time, and a roller moving knife was used to cut straw for the second time. ANSYS software was used to conduct static and modal analyses of the moving roller shaft and optimize the structure of the cutting part and the staggered arrangement of hammer claw. The first-order resonance frequency of the hammer claw shaft is 205.84 Hz, and the first-order natural frequency of the pulling roller moving knife mechanism is 214.35 Hz, which can avoid resonance and realize efficient picking and cutting of straw.Keywords: straw, hammer claw, roller moving knife mechanism, fixed knifeDOI: 10.25165/j.ijabe.20211406.6746Citation: Xu K, Ge Y Y, Xiao M H, Kang M, Ni J. Design of a straw picking and cutting device. Int J Agric & Biol Eng, 2021; 14(6): 93–98.